Global response of ship hull during ramming of heavy ice features - Broman, Mathias; Nordqvist, Per (Chalmers tekniska högskola / Institutionen för sjöfart och marin teknik, 2013)
The human presence in Arctic waters has increased and the development is assumed to continue. In order ensure that this increase in marine activities will be conducted in a safe manner, additional information about the factors that affect the marine structures in Arctic waters are required. This master’s thesis aims at analysing ice- induced global forces that affect a ship’s hull when colliding with heavy ice features. This was done in order to increase the knowledge of what structural loads a ship encounters during Arctic operations and thereby contribute to a safer development in the Arctic. This was carried out by creating a model that used recorded motions of a ship when it collided with a heavy ice feature in order to calculate the global forces that affect the ship hull. The motion data was collected by Det Norske Veritas during the Coldtech research project on board the Norwegian Coast Guard vessel KV Svalbard. To give an understanding and background to the problems that the model needs to handle, this thesis includes a brief review of sea ice properties and mechanics; ice class rules; and hull monitoring. These parts are used when the results are analysed and compared. In addition, the model developed is limited to squared collisions and the first impact sequence, since only then the impact location can be considered known. Furthermore, it is also assumed that the ship can be seen as a rigid body; this is a normal assumption when dealing with ship motions. The outcome of this study is a model that can be used for calculation of the iceinduced global forces that affect the ship’s hull when colliding with a heavy ice feature. The results using the model are compared with the design load from ice class rules, since the same impact type is considered. The results are also compared with previous work done in the area. From the comparisons it can be seen that the forces calculated with the current model seem to be reasonable as they are in the same order of magnitude. However, more measurements are required ...